Alterations of autophagy in the peripheral neuropathy Charcot-Marie-Tooth type 2B. Issue 6 (3rd June 2018) - Colecchia, David; Stasi, Mariangela; Leonardi, Margherita; Manganelli, Fiore; Nolano, Maria; Veneziani, Bianca Maria; Santoro, Lucio; Eskelinen, Eeva-Liisa; Chiariello, Mario; Bucci, Cecilia
ABSTRACT: Charcot-Marie-Tooth type 2B (CMT2B) disease is a dominant axonal peripheral neuropathy caused by 5 mutations in the RAB7A gene, a ubiquitously expressed GTPase controlling late endocytic trafficking. In neurons, RAB7A also controls neuronal-specific processes such as NTF (neurotrophin) trafficking and signaling, neurite outgrowth and neuronal migration. Given the involvement of macroautophagy/autophagy in several neurodegenerative diseases and considering that RAB7A is fundamental for autophagosome maturation, we investigated whether CMT2B-causing mutants affect the ability of this gene to regulate autophagy. In HeLa cells, we observed a reduced localization of all CMT2B-causing RAB7A mutants on autophagic compartments. Furthermore, compared to expression of RAB7A WT, expression of these mutants caused a reduced autophagic flux, similar to what happens in cells expressing the dominant negative RAB7A T22N mutant. Consistently, both basal and starvation-induced autophagy were strongly inhibited in skin fibroblasts from a CMT2B patient carrying the RAB7A V162M mutation, suggesting that alteration of the autophagic flux could be responsible for neurodegeneration.